PENGARUH PENGGUNAAN EKSTRAK KULIT BIJI KAKAO SEBAGAI BAHAN PENGAWET ALAMI BAKSO SAPI PADA PENYIMPANAN SUHU RUANG - Kayaputri, Indira Lanti; Y, Cahyana; T, Rialita; D, Kurniati; D. M, Sumanti; H.R, Arifin; S, Pratiwi; Gina, F (Unpad Press, 2023)
Meatball is a processed meat product that is easily damaged. Utilization of cocoa bean skin as a natural preservative is expected to increase the value of cocoa bean skin. The purpose of this study was to determine the exact concentration of the best cocoa bean extract as a natural preservative of cow meatballs at room temperature storage. The research method used is correlation regression method with 4 treatments and 2 replications. The treatment consisted of addition of cocoa bean extract with concentration 0%, 30%, 37,5%, and 45%. There was a correlation between the length of storage with the result of the cow meatballs observation which showed that the addition of cocoa bean extract with 30% concentration had the best characteristic, because at 24 hours total microbial 2,4 × 104 cfu / g, the amount of S. aureus bacteria equal to 1.0 × 102 cfu / g, and the number of E. coli bacteria of 9,0 × 101 cfu / g. The above components show the results of the analysis is still within the limits of SNI No. 01-3818-2014.